Enhanced involvement of general practitioners in cancer rehabilitation: a randomised controlled trial. Issue 2 (16th April 2012) - Bergholdt, Stinne Holm; Larsen, Pia Veldt; Kragstrup, Jakob; Søndergaard, Jens; Hansen, Dorte Gilså
Abstract : Objective: To test the hypothesis that a multimodal intervention giving the general practitioner (GP) an enhanced role in cancer rehabilitation improves patients' health-related quality of life and psychological distress. Design: Cluster randomised controlled trial. All general practices in Denmark were randomised to an intervention group or to a control group. Patients were subsequently allocated to intervention or control (usual procedures) based on the randomisation status of their GP. Setting: All clinical departments at a public regional hospital treating cancer patients and all general practices in Denmark. Participants: Adult patients treated for incident cancer at Vejle Hospital, Denmark, between 12 May 2008 and 28 February 2009. A total of 955 patients (486 to the intervention group and 469 to the control group) registered with 323 general practices were included. Intervention: The intervention included an interview about rehabilitation needs with a rehabilitation coordinator at the regional hospital, information from the hospital to the GP about individual needs for rehabilitation and an encouragement of the GP to contact the patient to offer his support with rehabilitation. Main outcome measures: The primary outcome was health-related quality of life measured 6 months after inclusion using the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30). Secondary outcomes included quality of life at 14 months and additional subscales of the EORTC QLQ-C30 at 6 and 14 months and psychological distress at 14 months using the Profile of Mood States Scale. Results: No effect of the intervention was observed on primary and/or secondary outcomes after 6 and 14 months. Conclusion: A multimodal intervention aiming to give the GP an enhanced role in cancer patients' rehabilitation did not improve quality of life or psychological distress. Trial registration: ClinicalTrials.gov, registration ID number NCT01021371 .